Household Preparedness for Natural Hazard Events in Central Java, Indonesia - Faruk, Fahrulraz M.; Wulandari, Ayu; Doven, Fransiska Sisilia; Budyanra, Budyanra (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
Socioeconomic aspects related to how households access to their basic needs. The ability of each household to vary affects how they respond to disasters. There have been many studies on how the effects of natural hazards on socio-economic aspects. Therefore, this research will use a different way by looking at the comparison between one indicator with another. How big is the ratio of households with good socioeconomic conditions with those who are not good at responding to natural hazard events? Descriptive analysis will describe how much the percentage of household preparedness in Central Java. While inferential analysis with binary logistic regression will explain socioeconomic variables that have a significant effect on household preparedness, and a comparison for each variable. This study finds the relationship between social-economic variables and household preparedness. Disaster preparedness from the poor households is different with those are not poor, as well as between those living in the urban or rural.